Improving Student Science Literacy on Environmental Pollution Materials Through the Application of an Integrated STEM Discovery Learning Model - Miftahul Hasanah; Usman Usman; Indria Wahyuni; Selfi Maharani; Indah Juwita Sari (Universitas Sultan Ageng Tirtayasa, 2026)
One of the problems in science education, particularly related to environmental pollution material, is the low level of students' science literacy. This study was conducted to determine the improvement of students' science literacy through the application of integrated STEM discovery learning, particularly on environmental pollution material. This study used a quasi-experimental method with an unequal control group design. The population used was all 10th grade students at State Senior High School 7 in Serang City in the 2025/2026 academic year. The research sample consisted of class X.1 as the experimental class and class X.5 as the control class. Random sampling was used to determine the research sample. Data collection techniques used tests in the form of multiple-choice questions and questionnaires. The data obtained were analyzed using a parametric test in the form of an Independent Sample T-test to test the hypothesis. The analysis results showed a value of 0.001 < 0.05, so H1 was accepted, indicating that integrated STEM discovery learning had an effect on improving students' science literacy on the subject of environmental pollution.